2009
DOI: 10.1371/journal.pgen.1000475
|View full text |Cite
|
Sign up to set email alerts
|

The Yeast Pif1 Helicase Prevents Genomic Instability Caused by G-Quadruplex-Forming CEB1 Sequences In Vivo

Abstract: In budding yeast, the Pif1 DNA helicase is involved in the maintenance of both nuclear and mitochondrial genomes, but its role in these processes is still poorly understood. Here, we provide evidence for a new Pif1 function by demonstrating that its absence promotes genetic instability of alleles of the G-rich human minisatellite CEB1 inserted in the Saccharomyces cerevisiae genome, but not of other tandem repeats. Inactivation of other DNA helicases, including Sgs1, had no effect on CEB1 stability. In vitro, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
403
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(429 citation statements)
references
References 72 publications
13
403
1
4
Order By: Relevance
“…Recent studies reported the formation of RNA/DNA hybrid G-quadruplexes during transcription that may modulate gene expression (54,55). Eukaryotic Pif1 has already been shown to bind and unwind G4 DNA structures (15)(16)(17)56). Its additional ability to unwind RNA:DNA structures may facilitate the resolution of the hybrid quadruplexes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies reported the formation of RNA/DNA hybrid G-quadruplexes during transcription that may modulate gene expression (54,55). Eukaryotic Pif1 has already been shown to bind and unwind G4 DNA structures (15)(16)(17)56). Its additional ability to unwind RNA:DNA structures may facilitate the resolution of the hybrid quadruplexes.…”
Section: Discussionmentioning
confidence: 99%
“…In yeast, Pif1 helicase is suggested to be involved in mitochondrial DNA recombination, repair, and replication (6,11). Some of its nuclear functions include Okazaki fragment processing (12,13), inhibition of rDNA replication (14), unwinding of G-quadruplex structures (15)(16)(17)(18), telomere regulation (19 -21), and repair of double-stranded DNA breaks (22)(23)(24)(25). S. cerevisiae Pif1 belongs to the superfamily (SF) 2 1B class of helicases.…”
mentioning
confidence: 99%
“…This human pathogen evades its host's immune system by changing the identity of its surface antigen via a G4 DNAinduced recombination event 10 . Importantly, however, this example also illustrates the recombinogenic and thus potentially pathological nature of this highly thermal stable non-B-DNA structure-a concern further fuelled by the notion of hampered DNA replication near G4 sequences in yeast [11][12][13] and the observed association of G4 motifs with structural genomic variations in human cancers 14 .…”
mentioning
confidence: 93%
“…12,14 ScPif1p also inhibits replication fork progression in rDNA, 15 plays roles in Okazaki fragment procession, 16 and participates in resolving G-quadruplex complexes. 17 Schizosaccharomyces pombe contains a PIF1 homolog, pfh1 + , 18 that encodes Pfh1p, which exists as multiple isoforms that localize to either nuclei or mitochondria and is essential for the maintenance of nuclear and mitochondrial DNA. 19 Pfh1p is required for the completion of DNA replication and for the proper response to DNA-damaging agents.…”
Section: Introductionmentioning
confidence: 99%